Impact of Blend Morphology on Interface State Recombination in Bulk Heterojunction Organic Solar Cells. (5th January 2015) - Bouthinon, Benjamin; Clerc, Raphaël; Vaillant, Jérôme; Verilhac, Jean‐Marie; Faure‐Vincent, Jérôme; Djurado, David; Ionica, Irina; Man, Gabriel; Gras, Antoine; Pananakakis, Georges; Gwoziecki, Romain; Kahn, Antoine
Abstract : This work is a reinvestigation of the impact of blend morphology and thermal annealing on the electrical performance of regioregular‐P3HT:PC60 BM bulk heterojunction organic solar cells. The morphological, structural, and electrical properties of the blend are experimentally investigated with atomic force microscopy, X‐ray diffraction, and time‐of‐flight measurements. Current–voltage characteristics of photodiode devices are measured in the dark and under illumination. Finally, the existence of exponential electronic band tails due to gap states is experimentally confirmed by measuring the device spectral response in the subband gap regime. This method reveals the existence of a large density of gap states, which is partially and systematically reduced by thermal annealing. When the band tails are properly accounted for in the drift and diffusion simulations, experimentally measured charge transport characteristics, under both dark and illuminated conditions and as a function of annealing time, can be satisfactorily reproduced. This work further confirms the critical impact of tails states on the performance of solar cells. Abstract : The predominance of the band tail states reorganization, characterized by spectral response measurement, in the improvement of the solar cell performances during the annealing step of the active layer is discussed. This energetic reorganization leads to a lowering of the recombinations assisted by trap state (efficiency improvement) and a decrease of the thermal generation from trap states (reverse dark current).